Farm to School of Park County : a journey from program to nonprofit, (B) - Cates, Karen L., (SAGE Business Cases., 2019)
The second in a four part case series, this case describes Farm to School's decision to enter into a fiscal sponsorship agreement with the local community foundation. The next task for the organization's leaders is recruiting founding board members. The organization must now decide whom to ask and how to do it.